Pembentukan Kata Compounding dalam Teks Eksposisi Siswa Kelas XI SMA Swasta Anastasia - Boisman Harefa; Dairi Sapta Rindu Simanjuntak; Asnita Hasibuan; Berman Hutahaean; Losten Tamba; Tania Repayona Br. Tarigan; Rika Br. Purba (Universitas Palan, 2026)
This study examines compounding in exposition texts written by Grade XI students of SMA Swasta Anastasia. The study is motivated by the importance of word formation processes in enriching vocabulary and improving students’ writing skills, particularly in expressing ideas clearly and systematically. This research aims to identify the forms and meanings of compound words used in students’ exposition texts. A qualitative descriptive method with content analysis was employed, and the data were analyzed based on the concept of compounding in morphological studies. The findings reveal that students use various types of compound words, including noun–noun combinations, adjective–noun combinations, and reduplication forms that produce new meanings. The results indicate that compounding contributes to meaning clarification and enhances students’ ability to communicate ideas effectively through written texts. However, students’ competence in using compound words is still developing and influenced by their linguistic environment and learning experiences. This study contributes to morphology research and Indonesian language education by highlighting the role of word formation in students’ writing development.